Chronic Recurrent Multifocal Osteomyelitis: Treatment with a Tumor Necrosis Factor-Alpha Inhibitor - André de Souza CAVALCANTI; Evaldo Gomes SENA; Sérgio Vasconcelos CAVALCANTI; Fernando de Souza CAVALCANTI; Ângela Luzia Branco Pinto DUARTE (Archives of Rheumatology, 2012)
Chronic recurrent multifocal osteomyelitis (CRMO), a non-bacterial osteitis (NBO), is a rare auto-inflammatory immune disorder. A delay in the diagnosis of this disease may cause irreversible damage to the skeletal system. The similarities among CRMO, Majeed syndrome, and chronic multifocal osteomyelitis (CMO) in mice strongly indicate a genetic basis. In this article, we present a 10-year-old boy with CRMO who was successfully treated with a tumor necrosis factor-alpha (TNF-a) inhibitor after conventional management had failed. Over a five-year period, he had experienced intermittent pain in his joints and been treated with non-steroidal anti-inflammatory drugs (NSAIDs). In a search for the cause of these symptoms, he was admitted to a pediatric orthopedic unit where he was diagnosed as having septic osteomyelitis. He underwent treatment with several antibiotics, however no improvement was seen and he was referred to a pediatric rheumatologist. Magnetic resonance imaging (MRI) and X-rays were crucial in the patient’s diagnosis. This case serves as an example of the need to emphasize prompt referrals for patients suspected of having CRMO so as to avoid bone damage and provide adequate management.